Sensory and motor differences in Autism Spectrum Conditions and developmental coordination disorder in children: a cross-syndrome study - Hannant, Penny; Cassidy, Sarah; Van de Weyer, Rosaline; Mooncey, Sophia (Elsevier, 2018)
Recent research has shown that Developmental coordination disorder (DCD) can present with some similar symptomology as Autism Spectrum Conditions (ASC). This paper therefore explored the similarities and differences in coordination and sensory responsivity between DCD and ASC. 77 children took part: 42 (35 male, 7 female) with ASC (ages 7–21: mean age 12.23 years), 26 (19 male, 7 female) with DCD (ages 7–21; mean age 11.07 years) and 9 (2 male, 7 female) with ASC and DCD (ages 8–15; mean age 12.27). All groups completed a battery of validated parent report measures online that included motor coordination (DCDQ), sensory responsivity (SPC-R) and social communication measures (AQ). Results showed no significant differences in coordination, and some significant differences in sensory responsivity between ASC and DCD (increased visual and auditory responsivity and decreased proprioception). Exploratory analysis showed that these differences showed good validity in identifying the diagnosis of ASC and DCD. These results elucidate the underlying causes of motor coordination difficulties in both conditions. Specifically, ASC coordination difficulties appear linked to visual processing impairments, whilst DCD coordination difficulties appear to be linked to spatial processing. This may aid better diagnosis and intervention for these conditions.